1875
DOI: 10.1242/jcs.s2-15.58.107
|View full text |Cite
|
Sign up to set email alerts
|

On Chlamydomyxa Labyrinthuloides, nov. gen. et sp., a New Freshwater Sarcodic Organism

Abstract: Some short time after the appearance of Cienkowski’s memoir on a new type of Sarcodic organisms met with by him in the sea (at Odessa), which he named Labyrinthuleæ, I was not a little surprised and interested on meeting with a form from the freshwater so wonderfully resembling those described by him, as, notwithstanding one circumstance, hereafter to be adverted to, even still to render it a matter of considerable question whether it may not truly belong to that group, even though it should not be congeneric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, we consider Penardia mutabilis Cash, 1904 (the type species of the genus) a junior synonym of Chlamydomyxa labyrinthuloides Archer, 1875, a well-characterized amoeboid alga that branches at the base of the Chrysophyceae (Grant et al, 2009;Wenderoth et al, 1999). This synonymy is supported by their isolation from the same environment (Sphagnum-dominated bogs), the presence of spindle-shaped granules shuttled along the anastomosing pseudopodia, and a cell body packed with yellow-green plastids (Archer, 1875;Cash, 1904;Cash & Hopkinson, 1905). Therefore, the name Penardia is not appropriate for vampyrellids, and "New Isolate NVam1" documented by Berney et al (2013) likely represents a yet-undescribed genus, given the marked genetic distance from S. perlucida as well as the substantial morphological differences.…”
Section: Discussionmentioning
confidence: 99%
“…However, we consider Penardia mutabilis Cash, 1904 (the type species of the genus) a junior synonym of Chlamydomyxa labyrinthuloides Archer, 1875, a well-characterized amoeboid alga that branches at the base of the Chrysophyceae (Grant et al, 2009;Wenderoth et al, 1999). This synonymy is supported by their isolation from the same environment (Sphagnum-dominated bogs), the presence of spindle-shaped granules shuttled along the anastomosing pseudopodia, and a cell body packed with yellow-green plastids (Archer, 1875;Cash, 1904;Cash & Hopkinson, 1905). Therefore, the name Penardia is not appropriate for vampyrellids, and "New Isolate NVam1" documented by Berney et al (2013) likely represents a yet-undescribed genus, given the marked genetic distance from S. perlucida as well as the substantial morphological differences.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Vampyrella closterii was already transferred to another genus, Gobiella Cienkowski, 1881, for unknown reasons (Cienkowski, 1881; Röpstorf et al, 1994). Gobiella has repeatedly been considered a vampyrellid genus (Cienkowski, 1881; Röpstorf et al, 1994; Valkanov, 1940), but an examination of the original description of its type species, G. borealis (Cienkowski, 1881), revealed that the latter closely resembles Chlamydomyxa labyrinthuloides , a heterokont, amoeboid alga (Archer, 1875; Wenderoth et al, 1999). Hence, we consider the genus name Gobiella inadequate for the studied strains (and vampyrellids in general) and establish the new genus Pseudovampyrella with two species.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable dimensions of FLEC cysts and cysts observed in the laboratory along with the vacuolated nature of both entities further supported our original inference. According to our single-cell sequencing results, however, the Green Lake FFRP is closely related to C. labyrinthuloides, which is known to have finely branched, reticulated pseudopodia, yellowish-brown to greenish-brown pigmentation ( Archer, 1875 ), be well vacuolated (vs. a single contractile vacuole), and an encystment stage called an aplanospore ( Wenderoth et al, 1999 ). Environmental DNA sequences also grouped with known C. labyrinthuloides .…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that, during winter, the metazoans will be sluggish due to low temperature, making them unlikely to be the lead cause of laminae disruption, and that the FFRP is the main cause of microfabric disruption. Evidence for this assertion is three-fold: (1) the relatively abundant FFRP have copious and far reaching reticulopods, like those known to rend biofilms (Bernhard and Bowser, 1992); (2) in the laboratory, they exhibit substantial (horizontal) migration rates, (3) heterotrophy can be induced in C. labyrinthuloides when light levels are Bernhard et al 10.3389/fmicb.2023.1210781 Frontiers in Microbiology 16 frontiersin.org low (Archer, 1875). Low light levels in GL are expected in winter due to the low angle of incident sunlight, short daylight periods, and, typically, ice cover.…”
Section: Do the Dmp Stromatolites Accrete?mentioning
confidence: 99%